Shedding of Trypanosoma cruzi Surface Molecules That Regulate Host Cell Invasion Involves Phospholipase C and Increases Upon Sterol Depletion - Loch, Leonardo; Onofre, Thiago Souza; Rodrigues, João Paulo Ferreira; Yoshida, Nobuko (Frontiers in Cellular and Infection Microbiology, 2021)
Metacyclic trypomastigote (MT) forms of Trypanosoma cruzi have been shown to release into medium gp82 and gp90, the stage-specific surface molecules that regulate host cell invasion, either in vesicles or in soluble form. Here, we found that during interaction of poorly invasive G strain with the host cell, gp82 and gp90 were released in vesicle-like forms, whereas no such release by highly invasive CL strain was observed. Shedding of vesicles of varying sizes by CL and G strains was visualized by scanning electron microscopy, and the protein profile of conditioned medium (CM) of the two strains was similar, but the content of gp82 and gp90 differed, with both molecules being detected in G strain as bands of high intensity in Western blotting, whereas in CL strain, they were barely detectable. Confocal images revealed a distinct distribution of gp82 and gp90 on MT surface of CL and G strains. In cell invasion assays, addition of G strain CM resulted in decreased CL strain internalization. Depletion of gp82 in G strain CM, by treatment with specific mAb-coupled magnetic beads, increased its inhibitory effect on CL strain invasion, in contrast to CM depleted in gp90. The effect of cholesterol-depleting drug methyl-β-cyclodextrin (MβCD) on gp82 and gp90 release by MTs was also examined. G strain MTs, untreated or treated with MβCD, were incubated in serum-containing medium or in nutrient-depleted PBS++, and the CM generated under these conditions was analyzed by Western blotting. In PBS++, gp82 and gp90 were released at lower levels by untreated MTs, as compared with MβCD-treated parasites. CM from untreated and MβCD-treated G strain, generated in PBS++, inhibited CL strain internalization. Treatment of CL strain MTs with MβCD resulted in increased gp82 and gp90 shedding and in decreased host cell invasion. The involvement of phospholipase C (PLC) on gp82 and gp90 shedding was also investigated. The CM from G strain MTs pretreated with specific PLC inhibitor contained lower levels of gp82 and gp90, as compared with untreated parasites. Our results contribute to shed light on the mechanism by which T. cruzi releases surface molecules implicated in host cell invasion.